ChemInform Abstract: Radical Based Strategy Toward the Synthesis of 2, 3‐Dihydrofurans from Aryl Ketones and Aromatic Olefins. Issue 14 (April 2015) - Naveen, Togati; Kancherla, Rajesh; Maiti, Debabrata
Abstract: The facile protocol allows the copper‐catalyzed annulation of aryl ketones with aromatic olefins to produce a wide variety of dihydrofurans.